Socialization of aquaponics techniques for business efficiency at Aling Hydroponic Farm, Sandakan Sabah Malaysia - S. Syamsia; Asriyanti Syarif; Siti Suliza Salamat; Ilmas Abdurofi; R. Rosanna; D. Darmawati d; Iradhatullah Rahim (ResearchGate, 2024)
Aquaponics is the application of integrated agricultural techniques between the cultivation of fish and vegetables that are environmentally friendly with efficient use of inputs and optimizing production. Aling Hydroponics Farm has long applied hydroponic techniques for cultivating vegetables, apart from also cultivating fish using fiber ponds. However, the application of these two techniques has not been integrated so that it is not efficient in using production inputs. This international collaborative community service activity aims to socialize aquaponic techniques to Aling Hidroponik Farm partners as an effort to increase the efficiency of resource use in farming. The method of implementing activities uses visits and discussions at hydroponic cultivation and fish cultivation locations. This activity was attended by lecturers from the Faculty of Agriculture, Muhammadiyah University of Makassar and lecturers from the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah, students and the community. The results of the activity showed that the participants were very enthusiastic about taking part in the activity, the participants actively asked questions and expressed opinions regarding the opportunities and obstacles to implementing the aquaponic system from economic and social aspects